Family History and Smoking on Coronary Heart Disease - Hendras Ratri Mustika; Marsanti, Avicena Sakufa; Widiarini, Retno (Jurnal Ilmiah Kesehatan (JIKA), 2024)
Cases of coronary heart disease in a private hospital in Madiun City in the last year have increased by 41% due to various risk factors. So researchers are interested in examining whether the incidence of coronary heart disease is correlated with family history and smoking. This research design is quantitative with a case-control approach. The population is all CHD sufferers in the period January-November 2022. The total population is 159 subjects, with a sample of 54 case subjects and 54 control subjects. The questionnaire method was used to collect data, and then the Chi-square test was used to analyze the data. The results of this study were that there was a significant relationship between smoking and the incidence of CHD (p-value = 0,034), and there was a family history of CHD incidence (p-value = 0,012) at Hospital X Madiun City. There is a need to provide outreach regarding efforts to prevent CHD to the public in order to reduce cases of CHD.